2022
DOI: 10.1093/gerona/glac023
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Measured Total Sedentary Time and Pattern of Sedentary Accumulation in Older Adults: Associations With Incident Cardiovascular Disease and All-Cause Mortality

Abstract: Background We examined associations of total duration and pattern of accumulation of objectively-measured sedentary behaviour (SB) with incident cardiovascular disease (CVD) and all-cause mortality among older adults. Methods Total sedentary time and eight sedentary accumulation pattern metrics were extracted from accelerometer data of 3991 Whitehall II study participants aged 60-83 years in 2012-2013. Incident CVD and all-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
8
2
Order By: Relevance
“… 3 In the Whitehall II study, incident CVD risk was not higher with higher total sedentary time (HR, 1.02 [95% CI, 0.88–1.19]) and longer MSBD (HR, 1.09 [95% CI, 0.98–1.23]) after adjusting for MVPA. 34 Differences between the present study findings and those in the literature could be attributable to differences in study population, devices used, placement, wear interval duration, and method of classifying SB.…”
Section: Discussioncontrasting
confidence: 79%
“… 3 In the Whitehall II study, incident CVD risk was not higher with higher total sedentary time (HR, 1.02 [95% CI, 0.88–1.19]) and longer MSBD (HR, 1.09 [95% CI, 0.98–1.23]) after adjusting for MVPA. 34 Differences between the present study findings and those in the literature could be attributable to differences in study population, devices used, placement, wear interval duration, and method of classifying SB.…”
Section: Discussioncontrasting
confidence: 79%
“…Both oxidative stress and inflammation can damage cellular structures and impair cellular functions, resulting in variations in PhA values [ 43 ]. Although previous studies have identified a relationship between SB patterns and outcomes, such as mortality [ 44 ] and physical function [ 45 ], in older populations, this study found no significant statistical relationship between SB patterns and PhA. Thus, despite the potential for speculation based on these pieces of evidence, the exact underlying physiological mechanisms remain unclear.…”
Section: Discussioncontrasting
confidence: 71%
“…The reference value was set at the median to ensure that the results were less sensitive to potential outliers or extreme values in the exposure distribution. Because total sedentary behavior is highly correlated with patterns of sedentary behavior accumulation, the sedentary behavior variables were analyzed in separate models for the secondary analyses . In addition, an analysis was included that used quartiles of sedentary behavior as an exposure.…”
Section: Methodsmentioning
confidence: 99%